Effects of bilateral lesions in the central amygdala on spontaneous baroreceptor reflex in conscious rats - Kei Tsukioka; Ko Yamanaka; Hidefumi Waki (Japanese Society of Physical Fitness and Sports Medicine, 2019)
The amygdala induces emotion and controls the cardiovascular system. We previously found that lesions in the central nucleus of amygdala (CeA), which is associated with negative emotion, chronically increase the arterial pressure (AP); however, the mechanism involved in this process remains unclear. In this study we compared the heart rate (HR), high frequency (HF) component of HR variability as an index of cardiac vagal outflow, and spontaneous baroreceptor reflex gain (sBRG) before and after the occurrence of bilateral lesions in CeA for further understanding of cardiovascular regulation by CeA. The results showed that CeA lesions induced a chronic decrease in HR and increase in sBRG, suggesting that CeA regulates the autonomic nervous system. Taken together with our previous results, CeA was shown to control AP and HR as well as baroreflex gain; however, the mechanisms controlling basal AP through CeA are likely to be independent of mechanisms for baroreflex gain control. These contradictory findings may partially explain the known diverse hemodynamic patterns of the amygdala in response to a variety of stress conditions.